European Legal view on Termination of Pregnancy - Siniša Franjić (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Pregnancy, another state or gravidity, is the state of a woman who carries a new being. The fertilization and ends with childbirth. The fertilized egg develops and goes through several different stages of development: embryo and fetus. Diagnosing pregnancy is based on safe and unsafe signs, and most reliable evidence that ultrasound. Pregnancy lasts nine months and the vast majority of women is well tolerated. Unfortunately, there are women who do not stand up well due to certain health complications that can occur, it is necessary to perform abortions. The task of this paper is to consider abortion the legal aspects.